Similar Inflammatory Adaptation in Women following 10 Weeks of Two Equalized Resistance Training with Different Muscle Action Duration. (15th June 2022) - Pinto, Kelerson Mauro de Castro; Diniz, Rodrigo César Ribeiro; Tourino, Frank Douglas; de Lacerda, Lucas Túlio; Bearzoti, Eduardo; Costa, Karine Beatriz; de Souza, Débora Maria Soares; Lima, Fernando Vitor; Rocha-Vieira, Etel; Chagas, Mauro Heleno; Talvani, Andre
Abstract : This study is aimed at evaluating the profile of inflammatory markers and components of redox regulation in untrained women after 10 weeks of resistance training using equalized protocols but different muscle action duration (MAD). Twenty-two women underwent progressive resistance training exercising the knee extensor muscles for 10 weeks—3x/week, with 3-5 sets of 6 repetitions at 50% of the 1 repetition maximum strength test (1RM), with a rest of 180 s between the series, following the training protocol (i) 5 s of concentric muscle action for 1 s of eccentric muscle action (5C-1E) and (ii) 1 s of concentric muscle action for 5 s of eccentric muscle action (1C-5E). Quadriceps muscle hypertrophy maximum strength (1RM) and redox regulation/muscle damage/inflammatory markers (CAT, SOD, TBARS, FRAP, CH, LDH, CXCL8, and CCL2) were evaluated. Plasma markers were evaluated before and 30 minutes after the first and last training sessions. A similar gain in hypertrophy and maximum strength was observed in both groups. However, in the 5C-1E, a significant major effect was observed for SOD (F 1.19 = 10.480, p = 0.004 ) and a significant major time effect, with a reduction in the last training session, was observed for CXCL8 (F 1.37 = 27.440, p < 0.001 ). In conclusion, similar protocols of resistance training, with different MAD, produced similar inflammatory and adaptive responses to strength training. As the training load is progressive, the maintenance of this inflammatory and redox regulation profile suggests an adaptive response to the proposed strength training.